Effect of Manure and Fertilizer Nitrogen Doses on Growth and Crop Kale Army (Ipomeae Reptan Poir) - Nurlina; Sri Hidayati; Nurul Huda (Agricultural Science, 2018)
This study aims to determine how far a combination of manure and urea fertilizer influence on the growth and yield of kale land. Percobahan do in the garden percobahan Merdeka University Faculty of Agriculture, Surabaya, in the village of the District Karah Jambangan Surabaya. This research method using Randomized Trial group (RAK) factorial arranged, composed of two factors, namely: manure with 3 levels of treatment and the provision of nitrogen fertilizer (urea) with three levels of treatment. Maing each treatment was repeated 3 times and each combination treatment consisting of two plants. The results show there is no interaction on manure and nitrogen fertilizer dosage in all parameters of both observation plant leaf number, plant height and fresh weight pertanaman.begitu also manure does not provide real pengarruh against all plant nitrogen fertilizer dosing significant effect on parameter above the number of leaves, plant height, fresh weight per plant.